Monitoring the Activity of Industrial Facilities Using Satellite Images of the Heat IR Range (2021)
The results of the development and testing of the methodology for automated processing of satellite images of medium spatial resolution in the heat and short-wave IR range are presented. For the specified test areas, digital maps of the Earth’s surface temperature were obtained for the territories where oil refineries and chemical plants are concentrated. A comparative analysis of the results of automated recognition of heat radiation sources showed a fairly high degree of correlation between the results of processing images of the heat IR range and the results of processing images of the short-wave IR range. We also compared the results of automated recognition of heat radiation sources based on images of the same territory taken from different satellites at different times. The results of testing the proposed methodology confirmed the possibility and high efficiency of using night images from the Terra satellite (ASTER survey instrument) and from the Landsat-8 satellite (TIRS survey instrument) to monitor the production activity of large industrial facilities that are sources of heat radiation. #CSOC1120 © 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.